The area of the ellipse
is given by
![\displaystyle\iint_E\mathrm dA=\iint_E\mathrm dx\,\mathrm dy](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Ciint_E%5Cmathrm%20dA%3D%5Ciint_E%5Cmathrm%20dx%5C%2C%5Cmathrm%20dy)
To use Green's theorem, which says
![\displaystyle\int_{\partial E}L\,\mathrm dx+M\,\mathrm dy=\iint_E\left(\frac{\partial M}{\partial x}-\frac{\partial L}{\partial y}\right)\,\mathrm dx\,\mathrm dy](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_%7B%5Cpartial%20E%7DL%5C%2C%5Cmathrm%20dx%2BM%5C%2C%5Cmathrm%20dy%3D%5Ciint_E%5Cleft%28%5Cfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20x%7D-%5Cfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20y%7D%5Cright%29%5C%2C%5Cmathrm%20dx%5C%2C%5Cmathrm%20dy)
(
denotes the boundary of
), we want to find
and
such that
![\dfrac{\partial M}{\partial x}-\dfrac{\partial L}{\partial y}=1](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20y%7D%3D1)
and then we would simply compute the line integral. As the hint suggests, we can pick
![\begin{cases}M(x,y)=\dfrac x2\\\\L(x,y)=-\dfrac y2\end{cases}\implies\begin{cases}\dfrac{\partial M}{\partial x}=\dfrac12\\\\\dfrac{\partial L}{\partial y}=-\dfrac12\end{cases}\implies\dfrac{\partial M}{\partial x}-\dfrac{\partial L}{\partial y}=1](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7DM%28x%2Cy%29%3D%5Cdfrac%20x2%5C%5C%5C%5CL%28x%2Cy%29%3D-%5Cdfrac%20y2%5Cend%7Bcases%7D%5Cimplies%5Cbegin%7Bcases%7D%5Cdfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20x%7D%3D%5Cdfrac12%5C%5C%5C%5C%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20y%7D%3D-%5Cdfrac12%5Cend%7Bcases%7D%5Cimplies%5Cdfrac%7B%5Cpartial%20M%7D%7B%5Cpartial%20x%7D-%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20y%7D%3D1)
The line integral is then
![\displaystyle\frac12\int_{\partial E}-y\,\mathrm dx+x\,\mathrm dy](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac12%5Cint_%7B%5Cpartial%20E%7D-y%5C%2C%5Cmathrm%20dx%2Bx%5C%2C%5Cmathrm%20dy)
We parameterize the boundary by
![\begin{cases}x(t)=5\cos t\\y(t)=17\sin t\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%28t%29%3D5%5Ccos%20t%5C%5Cy%28t%29%3D17%5Csin%20t%5Cend%7Bcases%7D)
with
. Then the integral is
![\displaystyle\frac12\int_0^{2\pi}(-17\sin t(-5\sin t)+5\cos t(17\cos t))\,\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac12%5Cint_0%5E%7B2%5Cpi%7D%28-17%5Csin%20t%28-5%5Csin%20t%29%2B5%5Ccos%20t%2817%5Ccos%20t%29%29%5C%2C%5Cmathrm%20dt)
![=\displaystyle\frac{85}2\int_0^{2\pi}\sin^2t+\cos^2t\,\mathrm dt=\frac{85}2\int_0^{2\pi}\mathrm dt=85\pi](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle%5Cfrac%7B85%7D2%5Cint_0%5E%7B2%5Cpi%7D%5Csin%5E2t%2B%5Ccos%5E2t%5C%2C%5Cmathrm%20dt%3D%5Cfrac%7B85%7D2%5Cint_0%5E%7B2%5Cpi%7D%5Cmathrm%20dt%3D85%5Cpi)
###
Notice that
kind of resembles the equation for a circle with radius 4,
. We can change coordinates to what you might call "pseudo-polar":
![\begin{cases}x(t)=4\cos^3t\\y(t)=4\sin^3t\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%28t%29%3D4%5Ccos%5E3t%5C%5Cy%28t%29%3D4%5Csin%5E3t%5Cend%7Bcases%7D)
which gives
![x(t)^{2/3}+y(t)^{2/3}=(4\cos^3t)^{2/3}+(4\sin^3t)^{2/3}=4^{2/3}(\cos^2t+\sin^2t)=4^{2/3}](https://tex.z-dn.net/?f=x%28t%29%5E%7B2%2F3%7D%2By%28t%29%5E%7B2%2F3%7D%3D%284%5Ccos%5E3t%29%5E%7B2%2F3%7D%2B%284%5Csin%5E3t%29%5E%7B2%2F3%7D%3D4%5E%7B2%2F3%7D%28%5Ccos%5E2t%2B%5Csin%5E2t%29%3D4%5E%7B2%2F3%7D)
as needed. Then with
, we compute the area via Green's theorem using the same setup as before:
![\displaystyle\iint_E\mathrm dx\,\mathrm dy=\frac12\int_0^{2\pi}(-4\sin^3t(12\cos^2t(-\sin t))+4\cos^3t(12\sin^2t\cos t))\,\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Ciint_E%5Cmathrm%20dx%5C%2C%5Cmathrm%20dy%3D%5Cfrac12%5Cint_0%5E%7B2%5Cpi%7D%28-4%5Csin%5E3t%2812%5Ccos%5E2t%28-%5Csin%20t%29%29%2B4%5Ccos%5E3t%2812%5Csin%5E2t%5Ccos%20t%29%29%5C%2C%5Cmathrm%20dt)
![=\displaystyle24\int_0^{2\pi}(\sin^4t\cos^2t+\cos^4t\sin^2t)\,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle24%5Cint_0%5E%7B2%5Cpi%7D%28%5Csin%5E4t%5Ccos%5E2t%2B%5Ccos%5E4t%5Csin%5E2t%29%5C%2C%5Cmathrm%20dt)
![=\displaystyle24\int_0^{2\pi}\sin^2t\cos^2t\,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle24%5Cint_0%5E%7B2%5Cpi%7D%5Csin%5E2t%5Ccos%5E2t%5C%2C%5Cmathrm%20dt)
![=\displaystyle6\int_0^{2\pi}(1-\cos2t)(1+\cos2t)\,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle6%5Cint_0%5E%7B2%5Cpi%7D%281-%5Ccos2t%29%281%2B%5Ccos2t%29%5C%2C%5Cmathrm%20dt)
![=\displaystyle6\int_0^{2\pi}(1-\cos^22t)\,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle6%5Cint_0%5E%7B2%5Cpi%7D%281-%5Ccos%5E22t%29%5C%2C%5Cmathrm%20dt)
![=\displaystyle3\int_0^{2\pi}(1-\cos4t)\,\mathrm dt=6\pi](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle3%5Cint_0%5E%7B2%5Cpi%7D%281-%5Ccos4t%29%5C%2C%5Cmathrm%20dt%3D6%5Cpi)
Answer: 90
Step-by-step explanation: if you subtract 35 from 125 you will get 90, which is your answer.
Answer:
f
(
x
)
=
3
(
x
−
1
)
2
+
5
Use the vertex form,
y
=
a
(
x
−
h
)
2
+
k
, to determine the values of
a
,
h
, and
k
.
a
=
3
h
=
1
k
=
5
Find the vertex
(
h
,
k
)
.
(
1
,
5
)
image of graph
Step-by-step explanation:
The longest side in a triangle is opposite the largest angle, and the shortest side is opposite the smallest angle.
So the smallest angle is <P.
Hope it may help :)
Answer:
B. -3,4
Step-by-step explanation: